Synthesis, characterization, and electrochemical and electrical properties of novel pentaerythritol-bridged cofacial bismetallophthalocyanines and their water-soluble derivatives - (:unkn) unknown (My University, 2007)
Novel cofacial bismetallophthalocyanines and their water-soluble derivatives were prepared. The precursor 4,4′-(2-phenyl-1,3-dioxane-5,5- diyl)bis(methylene)bis(oxy)-diphthalonitrile 3 was obtained by the reaction of [5-(hydroxymethyl)-2-phenyl-1,3-dioxan-5-yl] methanol 1 and 4- nitrophthalonitrile 2 with K2CO3 in DMF at 50°C. Cyclotetramerization was achieved by heating the homogenized mixture of the precursor, bisphthalonitrile, and Zn(OAc)2·2H2O or Co(OAc)2·4H2O at 300°C, which was followed by catalytic hydrogenation of the resulting product with Pd/C(10%) in DMF. The target water-soluble phthalocyanines were acquired from boiling suspensions of the compounds bearing eight OH side groups in aqueous KOH (20%) solution. The structure of the target compounds was confirmed by elemental analysis, FTIR, UV/Vis, 1H NMR, ICP-MS, and MALDI-TOF spectroscopic methods. The electrochemical and spectroelectrochemical measurements suggested the formation of various mixed-valent oxidation and reduction species, as a result of the strong intramolecular interactions between the two cofacial phthalocyanine units in the compounds. Impedance spectroscopy, dc conductivity, and thermopower measurements were performed using spin-coated films of these compounds as a function of temperature (290-440 K) and frequency (40-105 Hz). Dc conductivity showed typical Arrhenius behavior for all compounds. At low temperatures, a curved line was observed for the complex plane plots of impedance for all phthalocyanines. These curved lines transformed into a full semicircle with increasing temperature. The dependency of frequency exponent s on temperature suggested hopping-type conduction. A positive Seebeck coefficient was observed for all compounds, which indicates that the compounds behave as a p-type semiconductor. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.
Keywords: Cofacial configuration; Cyclic voltammetry; Phthalocyanines; Synthesis; Thermopower